2023
DOI: 10.1007/s00441-023-03780-8
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs contributing to the repair of tendon injury

Abstract: Tendon injury is one of the most common disorders of the musculoskeletal system, with a higher likelihood of occurrence in elderly individuals and athletes. In posthealing tendons, two undesirable consequences, tissue fibrosis and a reduction in mechanical properties, usually occur, resulting in an increased probability of rerupture or reinjury; thus, it is necessary to propose an appropriate treatment. Currently, most methods do not sufficiently modulate the tendon healing process and restore the function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…The present study on tendon damage repair utilising non-coding RNAs emphasizes the lack of comprehension regarding the control of tendon healing processes and the regulation of pertinent signaling pathways ( Lyu et al, 2023 ). Notable deficiencies include the absence of extensive data on how different cellular and signalling pathways impact the repair of tendons and the control of their constituents ( Ke and Zhang, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study on tendon damage repair utilising non-coding RNAs emphasizes the lack of comprehension regarding the control of tendon healing processes and the regulation of pertinent signaling pathways ( Lyu et al, 2023 ). Notable deficiencies include the absence of extensive data on how different cellular and signalling pathways impact the repair of tendons and the control of their constituents ( Ke and Zhang, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-144-3p plays a significant role in regulating tenocyte proliferation and migration during tendon repair ( Song et al, 2022 ). It is enriched in exosomes derived from tendon stem cell (TDSCs)and promote these cellular processes by targeting AT-rich interactive domain 1A (ARID1A) ( Lyu et al, 2023 ). On the other hand, it upregulates PTEN, which is involved in the PTEN/mTOR/TGF-β1 signaling cascades, crucial for tendon healing ( Song et al, 2022 ).…”
Section: Mirna and Tendon Injurymentioning
confidence: 99%
“…Although increased cell proliferation can be a positive result in the context of wound healing, other studies have suggested that the excessive upregulation of RhoA activity can also have tumorigenic or pro-senescent effects, thus indicating the need for further research to clarify its role in tendinous healing [109,110]. Furthermore, Xu et al also found that ASC-Exos treatment led to theupregulation of miR-148a, which has been associated with improved angiogenesis via the upregulation of the thrombospondin-4 gene and the downregulation of Kruppel-like factor 6 (KLF6) [39,111,112]. However, it is unclear whether, instead of inducing tendinous healing, miR-148a can propagate excess angiogenesis and thus induce a pathological state of tendinopathy [111,112].…”
Section: Micrornasmentioning
confidence: 99%
“…Furthermore, Xu et al also found that ASC-Exos treatment led to theupregulation of miR-148a, which has been associated with improved angiogenesis via the upregulation of the thrombospondin-4 gene and the downregulation of Kruppel-like factor 6 (KLF6) [39,111,112]. However, it is unclear whether, instead of inducing tendinous healing, miR-148a can propagate excess angiogenesis and thus induce a pathological state of tendinopathy [111,112]. Lastly, Shen et al concluded that the conversion of M1 to M2 macrophages that was observed after priming ASC-Exos with IFN-γ could be attributed to the upregulation of miR-146a-a response that has been observed by previous studies as well [40,113,114].…”
Section: Micrornasmentioning
confidence: 99%
“…Tendon injury can result from prolonged exercise, inappropriate training, lack of muscle strength, or muscle imbalance, so that is a common clinical problem and is often difficult to fully recover [ 3 ]. It may be due to its special tissue type, few blood vessels and cells [ 4 ], and still face the possibility of re-fracture after surgery [ 5 ], coupled with limited understanding of it, leading to some treatment delays, resulting in unsatisfactory clinical treatment results [ 6 , 7 ]. Therefore, understanding tendon injury and regeneration mechanisms can contribute to the study of tendon healing and repair.…”
Section: Introductionmentioning
confidence: 99%